The Role of Metta and Karuna Values in Buddhist Leadership on Prosocial Work Behavior - Prasetio, Meriyawaty Amelia; Asih, Situ; Albert, Albert (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
his study examines the effects of Metta and Karuna values in Buddhist leadership on Prosocial Work Behavior, with Value Congruence as a mediating variable, within the Indonesian Buddhist Representative Organization (WALUBI). A quantitative survey approach was employed. The research population comprised leaders and active members of WALUBI, from which 150 respondents were selected using a purposive sampling technique based on organizational involvement criteria. The study utilized primary data collected through a structured questionnaire distributed both directly and online. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS software. The findings reveal that Metta Leadership positively influences Value Congruence but does not directly affect Prosocial Work Behavior. In contrast, Karuna Leadership has a positive and significant effect on both Value Congruence and Prosocial Work Behavior. Furthermore, Value Congruence significantly affects Prosocial Work Behavior, acting as a full mediator in the relationship between Metta Leadership and Prosocial Work Behavior, and as a partial mediator in the relationship between Karuna Leadership and Prosocial Work Behavior. These results indicate that Buddhist leadership values require processes of internalization and value alignment to be effectively translated into prosocial work behavior. The study contributes theoretically to the literature on spiritual and Buddhist leadership by highlighting the strategic role of Value Congruence as a key mechanism linking leadership values and prosocial behavior. Practically, the findings provide insights for non-profit religious organizations to strengthen the integration of leadership values into organizational practices in order to foster sustainable prosocial work behavior.